Impact of different palliative systemic treatments on skeletal muscle mass in metastatic colorectal cancer patients. Issue 5 (24th August 2018) - Kurk, Sophie A.; Peeters, Petra H.M.; Dorresteijn, Bram; de Jong, Pim A.; Jourdan, Marion; Kuijf, Hugo J.; Punt, Cornelis J.A.; Koopman, Miriam; May, Anne M.
Abstract: Background: Observational studies suggest that loss of skeletal muscle mass (SMM) is associated with chemotherapy‐related toxicity, poor quality of life, and poor survival in metastatic colorectal cancer (mCRC) patients. Little is known about the evolution of SMM during palliative systemic therapy. We investigated changes in SMM during various consecutive palliative systemic treatment regimens using repeated abdominal computed tomography scans of mCRC patients who participated in the randomized phase 3 CAIRO3 study. Methods: In the CAIRO3 study, mCRC patients with stable disease or better after 6 cycles of first‐line treatment with capecitabine + oxaliplatin + bevacizumab (CAPOX‐B) were randomized between maintenance treatment with capecitabine + bevacizumab (CAP‐B) or observation. Upon first disease progression, in both groups, CAPOX‐B or other treatment was reintroduced until the second disease progression, which was the primary study endpoint. We analysed 1355 computed tomography scans of 450 (81%) CAIRO3 patients (64 ± 9.0 years, CAP‐B n = 223; observation n = 227) for SMM at four time points (i.e. prior to the start of pre‐randomization initial treatment, at randomization, and at first and at second disease progression) using the Slice‐o‐matic software and single slice evaluation at the lumbar 3 level. By using accepted and widely used formulas, whole body SMM was calculated. A linear mixed effects model, adjusted for relevant confounders, was used to assess SMM changes for the total group and within and between study arms. Results: During 6 cycles of initial treatment with CAPOX‐B prior to randomization, SMM decreased significantly in all patients [CAP‐B arm: −0.53 kg (95% CI −1.12; −0.07) and observation arm: −0.85 kg (−1.45; −0.25)]. After randomization, SMM recovered during CAP‐B treatment by 1.32 kg (0.73; 1.90) and observation by 1.20 kg (0.63; 1.78) (median time from randomization to first disease progression 8.6 and 4.1 months for CAP‐B arm and observation arm, respectively). After first progression and during reintroduction treatment with CAPOX‐B or other treatment, SMM again decreased significantly and comparable in both arms, CAP‐B: −2.71 kg (−3.37; −2.03), and observation: −2.01 kg (−2.64; −1.41) (median time from first progression until second progression CAP‐B arm: 4.7 months and observation arm: 6.6 months). Conclusions: This longitudinal study provides a unique insight in SMM changes in mCRC patients during palliative systemic treatment regimens, including observation. Our data show that muscle loss is reversible and may be influenced by the intensity of systemic regimens. Although studies have shown prognostic capacity for SMM, the effects of subsequent changes in SMM are unknown and may be clues for new future therapeutic interventions.